The chinesenization of American zoning in the 1980s: From Shanghai Hongqiao experiment to Wenzhou old town renewal - Shen, Yun; Hou, Li (International Planning History Society Proceedings, 2018)
The most instrumental reform in Chinese urban planning system during the market reform in the 1980s is the introduction of so-called “regulatory detailed planning” (in Chinese pinyin, kong gui), an adaptive form of American zoning in Chinese cities. However, this episode of the reform hasn’t been closely examined from a historic and critical perspective so far. Based on archival research, mapping and interviews, this article traces the planning and development process of Shanghai Hongqiao New District and Wenzhou old town, and explores the original process of transplantation and localization of American zoning in Chinese cities. By comparing the planning and construction explorations of the two cities, we will argue that although it learned much from zoning techniques, especially the control indexes, the regulatory detailed planning is more to be a plat form for local government to negotiate with the foreign businessmen and other private sectors, rather than representing public intervention and regulation in the US, and served as a technical tool to materialize the development goals of Chinese cities.